2023
DOI: 10.1038/s41467-023-36984-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of protection and viral load trajectories in omicron breakthrough infections in triple vaccinated healthcare workers

Abstract: Vaccination offers protection against severe COVID-19 caused by SARS-CoV-2 omicron but is less effective against infection. Characteristics such as serum antibody titer correlation to protection, viral abundance and clearance of omicron infection in vaccinated individuals are scarce. We present a 4-week twice-weekly SARS-CoV-2 qPCR screening in 368 triple vaccinated healthcare workers. Spike-specific IgG levels, neutralization titers and mucosal spike-specific IgA-levels were determined at study start and qPCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…After regression analysis adjusting for age, sex, and home SARS-CoV-2 risk score, only bAb levels retained statistical significance (p-value of 0.025) with the p-value for NTs to BA.1.1 increasing to 0.056. The finding that bAb levels correlate as well or better than NTs has been observed in a number of other studies ( 11 , 12 , 14 ). Interestingly, a study that incorporated data from seven clinical studies of four different vaccine platforms found that IgG bAb levels induced by the different vaccines correlated better than NTs in explaining differences in vaccine efficacy ( 13 ).…”
Section: Discussionsupporting
confidence: 77%
“…After regression analysis adjusting for age, sex, and home SARS-CoV-2 risk score, only bAb levels retained statistical significance (p-value of 0.025) with the p-value for NTs to BA.1.1 increasing to 0.056. The finding that bAb levels correlate as well or better than NTs has been observed in a number of other studies ( 11 , 12 , 14 ). Interestingly, a study that incorporated data from seven clinical studies of four different vaccine platforms found that IgG bAb levels induced by the different vaccines correlated better than NTs in explaining differences in vaccine efficacy ( 13 ).…”
Section: Discussionsupporting
confidence: 77%
“…After regression analysis adjusting for age, sex, and home SARS-CoV-2 risk score, only bAb levels retained statistical significance (p value of 0.025) with the p value for NTs to BA.1.1 increasing to 0.056. The finding that bAb levels correlate as well or better than NTs has been observed in a number of other studies 11,12,14 . Interestingly, a study that incorporated data from 7 clinical studies of four different vaccine platforms found that IgG bAb levels induced by the different vaccines correlated better than NTs in explaining differences in vaccine efficacy 13 .…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, while during pre-Delta and Delta pandemic waves, studies showed protection against infection in individuals with anti-RBD titers ranging from 154 binding antibody units (BAU)/mL (95% CI 42-559) [25] to 168.2 BAU/mL [31], and studies performed during the Omicron period showed a protective effect at higher titers, from 1235 [30] to 3035 BAU/mL [8]. During this period, studies showed that antibody levels greater than 2000 BAU/mL (compared to titers lower than 500 BAU/mL) [24] and anti-Spike antibody levels greater than 2816.0 BAU/mL (compared to titers lower than this cut-off) [28] were less likely to become infected, with a 50% reduction in the odds of breakthrough infection.…”
Section: Resultsmentioning
confidence: 99%
“…While the lack of standardized, well-validated assays to measure T cell responses has hindered the evaluation of specific T cell responses as a correlate of protection in large-scale settings [7], in the absence of a well-defined humoral CoP, serological testing also cannot be used to confirm immune protection. This has been further complicated by the emergence of variants of concern (VOCs) that have shown high rates of breakthrough infections in previously fully vaccinated subjects [8].…”
Section: Introductionmentioning
confidence: 99%